Accelerated Oxalosis Contributing to Delayed Graft Function after Renal Transplantation - Yvelynne P. Kelly; Astrid Weins; Melissa Y. Yeung (Case Reports in Transplantation)
Hyperoxaluria is an important and underrecognized cause for allograft dysfunction and loss after transplantation. It is potentially treatable if recognized in a timely fashion. Research is ongoing to expand the array of therapeutic options available to treat this. We present a case of a 59-year-old gentleman who underwent deceased donor renal transplantation that was complicated by delayed graft function necessitating continuation of renal replacement therapy. His initial biopsy showed extensive acute tubular necrosis with associated peritubular capillaritis and interstitial nephritis and oxalate crystals in several tubules. Despite receiving methylprednisolone to treat moderate acute cellular rejection, he remained dialysis dependent with minimal urine output. An interval renal allograft biopsy revealed residual acute tubular necrosis with extensive oxalate crystals now visible in many tubules. His plasma oxalate level was concurrently elevated to 19.3 μmol/L (reference range ≤ 1.9 μmol/L). He commenced calcium citrate to manage his hyperoxaluria and ultimately became dialysis independent at 3 weeks after transplantation. This case provides an important example of accelerated oxalate nephropathy as an underappreciated contributor to delayed graft function after renal transplantation. Our accompanying discussion provides an update on current therapeutic measures for managing this challenging condition.